Selection of Elite Broad Leaf Mustard (Brassica juncea var. rugosa) (L.) Czern. Genotypes in the Mid-hill Condition of Dailekh District, Nepal - Chalise, Basanta; Pun, Tula Bahadur; Shrestha, Surendrea Lal (Nepalese Horticulture, 2020)
An experiment was carried out on six genotypes of Broad Leaf Mustard (Brassica juncea var. rugosa) (L.) Czern. namely 'HRDBLM-001', 'HRDBLM-003', 'HRDBLM-005', 'HRDBLM-007', 'Marpha Broad Leaf' and 'Khumal Broad Leaf' at Horticultural Research Station, Kimugaun, Dailekh, during two consecutive years 2013 and 2014 to identify promising genotypes collected from different parts of Nepal under the Coordinated Varietal Trial (CVT). The experiment was laid out in Randomized Complete Block Design (RCBD) consisting of four replications per treatment. The result revealed that among the six genotypes tested ‘HRDBLM-005' (39.78 mt/ha), 'HRDBLM-007' (34.96 mt/ha) and ‘HRDBLM-001’ (32.36 mt/ha) were found superior.